Responses of lactating Holstein cows to low-pressure soaking or high-pressure misting during heat stress - Joseph P. Harner; John F. Smith; W.F. Miller; B. Cvetkovic (Kansas Agricultural Experiment Station Research Reports, 2004)
Lactating dairy cattle were used to evaluate three different cooling systems. Eight cows were arranged in a replicated Latinsquare design and assigned to each of four treatments. Treatments were control, lowpressure soaking (LPS), high-pressure misting with 1.7 gallons per minute of water (HP-1.7), or high-pressure misting with 3.4 gallons per minute of water (HP-3.4). Cows were allowed to become heat stressed in a free-stall facility, and then were moved to a tie-stall barn for 2 hours of observations during four hot and humid afternoons. Respiration rates declined when heat abatement systems were used. Respiration rates at the end of the observation period were reduced by 20, 36, and 48% for HP-1.7, HP-3.4, and LPS, respectively. Rearudder skin surface temperature was reduced at a faster rate under the HP-4 treatment than with LPS, but the two treatments did not differ in final rear-udder skin surface temperature or vaginal temperature. The HP-3.4 treatment used the greatest amount of water during the 2-hour testing period. The result was a combination of air-cooling and soaking. Results indicated that a combination of air cooling and soaking may result in faster reduction of surface temperature. When only air cooling was used (HP-1.7), heat stress was reduced, but it was less effective than either LPS or HP-3.4. Use of a low-pressure soaking system is superior to high-pressure misting unless cattle become soaked by the high-pressure system.; Dairy Day, 2004, Kansas State University, Manhattan, KS, 2004;
Keywords: Dairy Day; 2004; Kansas Agricultural Experiment Station contribution; no. 05-112-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 941; Dairy; Heat stress abatement; Cow comfort; Cow cooling